2010
DOI: 10.1111/j.1537-2995.2009.02559.x
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 8 genomes and seroprevalence in United States blood donors

Abstract: The results indicate that the prevalence of detectable HHV-8 genomes in healthy blood donors is very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 34 publications
4
26
1
Order By: Relevance
“…As seen in other studies, we found a significantly higher seroprevalence of HHV8 in HIV-positive compared to HIV-negative individuals [25,26]. Additionally, we found a slightly higher seroprevalence in men compared to women, but this trend was not statistically different; this is also in concordance with other studies [22,27].…”
Section: Discussionsupporting
confidence: 82%
“…As seen in other studies, we found a significantly higher seroprevalence of HHV8 in HIV-positive compared to HIV-negative individuals [25,26]. Additionally, we found a slightly higher seroprevalence in men compared to women, but this trend was not statistically different; this is also in concordance with other studies [22,27].…”
Section: Discussionsupporting
confidence: 82%
“…It was found that none of the 738 blood samples, including those from the 18 oral shedders, were positive for HHV-8 DNA, despite triplicate testing, confirming earlier findings that in KS non-endemic areas, HHV-8 detection in peripheral blood is very rare, even among HHV-8-seropositive individuals such as blood-bank donors [10,11]. Blood donation by MSM has raised concerns about the possibility of HHV-8 transmission, and in some settings, it has been proposed to impose a lifetime donation deferral for this group [12].…”
Section: Discussionsupporting
confidence: 77%
“…Oral samples have been consistently shown to have the highest rates of HHV-8 viral detection compared to semen, urine, urethral, vaginal, and anal samples, suggesting that saliva may play an important role in HHV-8 transmission [29]. On the other hand, transmission through blood and blood transfusion remains a controversial issue with no conclusive evidence [1012]. Studies among blood donors outside KS endemic areas have shown very rare detection of HHV-8 DNA in blood samples, even among HHV-8-seropositive individuals [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, HHV-8 seroprevalence is low, and it peaks during the period of highest sexual activity (12). Studies of healthy blood donors in the United States have reported HHV-8 seroprevalence of 3.9% to 7.3% (13).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%